METHODOLOGICAL APPROACH TO PLANNING THE RECONSTRUCTION OF URBAN ENVIRONMENT - Bredikhina, Natalia Vladimirovna; Ivanovich , Matreninsky Sergey; Petrovna, Gorbaneva Elena Petrovna; Valerievich, Mishchenko Andrey (Journal of Applied Engineering Science, 2022)
The article substantiates the need for a comprehensive multidimensional reconstruction of the territories of cities and settlements, caused by social, urban planning and economic reasons. For effective planning of the reconstruction of sections of the urban environment, a systematic approach is proposed as a leading methodology, which allows one to design interrelated solutions for the reorganization of various objects of the urban environment in order to bring them in line with current norms and modern requirements. At the same time, sections of the urban environment are presented in the form of a complex hierarchical system - a system-integrated urban planning education - and are expressed by a subject structure with components and objects included in it. Physical deterioration, obsolescence, "technical comfort" are taken as indicators of the effectiveness of the functioning and development of a system-integrated urban planning education. Based on a systematic approach, a stratified mathematical model for the choice of options for actions, technical and technological solutions has been developed when designing the reconstruction of urban areas with minimization of resource consumption.